Trail log - 2000-2004 - Rolston, Holmes, 1932-2025, author (Colorado State University. Libraries, 2000)
Rolston accounts of: Antarctica, 2000 Yellowstone wolves. Backroads China, 2000. Brazil: Campo Grande and Pantanal. Churchill, Manitoba, and northern lights, 2001. Llama packing, Escalante Canyon, Utah. Guam and Inter-Pacific Science Congress. Spain. Edinburgh. Ethiopia and Uganda, 2003, Gorillas and chimpanzees. Bob Marshall Wilderness, North Chinese Wall, July 2003. Taiwan, March 2004. Teaching, spring term, Washington and Lee University. Lexington, VA, Yosemite National Park, and California Bar Association, Environmental Law.